ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR TESTING DISSOLUTION OF DIGOXIN TABLET USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Maryati, Leni
Digoxin is commonly used to treat heart failure. Digoxin is drug with a narrow therapeutic window. According to the Indonesian Pharmacopoeia IV, digoxin tablets dissolution was tested in 0.1 N HCI medium using fluorometric method. In this dissolution medium, digoxin could be hydrolyzed into compounds having cardioactivity lower than digoxin. Fluorometric method requires a longer time for preparation. Long time consumption and complicated sample preparations made this method less efficient and less effective so another alternative method is required. High Performance Liquid Chromatography (HPLC) with detection wavelength: 220 nm has been developed for this purpose. The columns used Symmetry@ Waters column RP - C18 3.9 mm x 150 mm, with a particle size of 5 um. A mixture of acetonitrile: water (26 : 74) was used as mobile phase with a flow rate: I mL/min and an injection volume of 100 uL. The method showed a good linearity at concentration range 0.128 ug/mL — 0,642 ug/mL with correlation coefficient 0.9997. The limit of detection and limit of quantitation were 0.0182 ug/mL and 0.0552 ug/mL. Intra-day and inter-day precision was good with HorRat : 0.573 and 0.626 respectively. The average ofpercent recovery was 99.43 % with the lowest levels: 93.82 % and the highest level: 109.60 %. According to the acceptance value of the validation indicated that this method was selective, accurate, precise, linear, robust and hence suitable for routine evaluation of digoxin tablet dissolution test.